Penerapan Akuntansi untuk Pajak Penghasilan (PPh) Pasal 21Pada Puskesmas Palengaan Pamekasan - Malia, Evi (Unversitas Islam Madura, 2016)
Income tax (PPh) Pasal 21 is the tax payable on the income become the taxpayer's liability to pay for it. The earnings in question, namely in the form of salary, honorarium, benefits and other payments with any name with respect to the work, services or activities performed by private people tax payers in the country. Law No. 36 Year 2008 which are used in determining the tax rate and payment procedures. The purpose of this research is to know the application of PPh 21 income tax accounting and the presentation of his report on public health Palengaan Pamekasan and to know the analysis calculation of the PPh Pasal 21 and wages accounting employees at Clinics Palengaan Pamekasan. The methods used in this research is descriptive method quantitative. The research indicates that the application of accounting for income taxes income tax pasal 21 at clinics palengaan i.e. upper cuts, remittance income tax pasal 21 and penjurnalannya, PPh pasal 21 allowances that are actually covered by employer health centers incorporated first into the elements of employee salary and benefits when the calculation of income tax pasal 21 carried out ( income tax pasal 21calculated joined him). As well as the calculation of income tax (PPh) pasal 21di Palengaan Pamekasan Clinics there are differences between the calculations performed in Clinics with the calculation done researchers based on the provisions of the legislation of taxation.